Eruca sativa plants modulate growth and gas exchange when cultivated under salinity stress after leaching fractions - Silva, Thayse Valéria e; Carneiro, Paulo Torres; Santos, Valdevan Rosendo dos; Silva, Ricardo Barros; Neto, Gilberto da Cruz Gouveia; Pavão, Jessé Marques da Silva Júnior (Journal of Aridland Agriculture, 2023)
The physiology of rocket plants at different salinity levels through irrigation water and leaching fractions was assessed. Four salinity levels of irrigation water: 0.10, 1.60, 3.10 and 4.60 dS m-1 and three leaching fractions: 0, 10 and 20% were applied. The physiological variables analyzed were photosynthetic rate, stomatal conductance, transpiration rate and photosynthetic pigment contents. The growth and biomass production were analyzed by: plant height, number of leaves, leaf area and partitioned and total plant fresh and dry mass, and root to aerial part ratio. The leaching fraction of 10% combined with irrigation with water salinity levels ranging from 0.10 to 0.88 dS m-1 resulted in greater plant height, leaf area and root, shoot and total dry mass. The leaching fraction of 20% with irrigation water with salinity levels from 0.10 to 2.7 dS m-1 generates higher leaf number, shoot fresh mass, root-to-shoot ratio, stomatal conductance, and photosynthetic rate. Irrigation water with a salinity level of 0.10 dS m-1 provides a higher transpiration rate for rocket plants. Irrigation water with a salinity level of 4.6 dS m-1 generates higher chlorophyll a, b and total (a + b) and carotenoid contents in rocket plants.